Protein–Polymer Conjugation via Ligand Affinity and Photoactivation of Glutathione S‑Transferase - Lin, En-Wei; Boehnke, Natalie; Maynard, Heather D (Bioconjugate chemistry, 2014)
A photoactivated, site-selective conjugation of poly(ethylene glycol) (PEG) to the glutathione (GSH) binding pocket of glutathione S-transferase (GST) is described. To achieve this, a GSH analogue (GSH-BP) was designed and chemically synthesized with three functionalities: (1) the binding affinity of GSH to GST, (2) a free thiol for polymer functionalization, and (3) a photoreactive benzophenone (BP) component. Different molecular weights (2 kDa, 5 kDa, and 20 kDa) of GSH-BP modified PEGs (GSBP-PEGs) were synthesized and showed conjugation efficiencies between 52% and 76% to GST. Diazirine (DA) PEG were also prepared but gave conjugation yields lower than for GSBP-PEGs. PEGs with different end-groups were also synthesized to validate the importance of each component in the end-group design. End-groups included glutathione (GS-PEG) and benzophenone (BP-PEG). Results showed that both GSH and BP were crucial for successful conjugation to GST. In addition, conjugations of 5 kDa GSBP-PEG to different proteins were investigated, including bovine serum albumin (BSA), lysozyme (Lyz), ubiquitin (Ubq), and GST-fused ubiquitin (GST-Ubq) to ensure specific binding to GST. By combining noncovalent and covalent interactions, we have developed a new phototriggered protein–polymer conjugation method that is generally applicable to GST-fusion proteins.